List of patentees to whom patents were issued by the Philippines Patents Office during the period 1948-1961 with a subject index to patents - Dumangas, Marianita L. (1974)
Inventions have largely contributed to the industrial progress of nations. They have been vital sources of technical information embodied in documents, patents have revealed varied, useful and specially new trends. in pure and applied sciences.